Assesment of the impact of service quality on customer satisfaction and loyality in banking Sector in Tanzania: Case of Diamond trust bank (Ltd) Tanga - Tarimo, Lilian (Mzumbe University, 2024)
A dissertation submitted to partial fulfillment of the requirements for the degree of Master of Business Administration and Corporate Management (MBA-CM) of Mzumbe University